Preliminary design chart of cement column for deep soil mixing method in tropical peat - Duraisamy, Youventharan (2010)
Peat and organic soils also categorized as soft soil. Application of cement column will leads to some changes in properties of peat. This report presents the effects of cement columns in terms of compressibility and shear strength in tropical peat. This report also discussed the engineering properties of unstabilized and stabilized tropical peat of east and west coast of Peninsular Malaysia. Samples from different locations were collected to distinguish the variants of organic content and fiber content in this study. Tropical peat collected from this location is classified as fibrous peat using Von Post scale. The moisture content and organic content of this peat is ranging from 400 % up to 900 % and 80 % to 90 % respectively. Author also found a good correlation between the engineering properties and the compressibility parameters. A dosage rate of 150 kg/m3 was used to mixed binders in various ratios. A column with 50 mm in diameter and 150 mm in length is applied into the soil. The compressibility and shear strength of unstabilized and stabilized peat was compared to determine the effectiveness of cement columns. The compressibility of peat was determined using conventional oedometer test and the undrained shear strength, Su of peat was determined using unconfined compressive strength test. Compressibility indices, Cc and Ca were identified as two crucial parameters to estimate settlements in peat. Based on the results obtained, the mixing of cement column in peat extensively increases the shear strength and significantly reduces the compressibility of peat compare to the unstabilized peat. Thus, preliminary design charts for cement columns were established as a guideline to engineers and academicians.